Simulasi Perubahan Prilaku Regangan Geser Material Rel Pada Perubahan Suhu Permukaan Kontak Akibat Beban Gelinding/Gesek - Widiyarta, I Made (Jurnal Energi Dan Manufaktur, 2012)
Repeated wheel load over rail can cause rail material at the contact surface to accumulate severe plasticdeformation. The material fails after accumulating a critical shear strain and produce wear debris and fatigue cracks. Duringrolling/sliding contact between railway rails and wheel, temperature will rais at the contact surface due to frictional heatingand thermal stress will develop. If the generation of heat is high enough the rail material may soften.In this work, a simulation based on ratchetting failure is used to study shear strain behaviour of rail material withfrictional heating in rolling/sliding contact between wheel and railway rail. The simulation results show the materialsoftening and thermal stress increase the rate of shear strain accumulation by ratchetting leading to fail material morequickly.
Keywords: rolling/sliding contact, frictional heating, softening, thermal stress, shear strain.